ETIOLOGY, FREQUENCY AND CLINICAL MANIFESTATIONS OF PURULENT INFLAMMATION OF THE FINGER JOINT IN SPORT HORSES (Academicia Globe: Inderscience Research, 2021)
Clinically examined 203 horses from farms of the Samarkand region, of which 30 (14.7%) animals were diagnosed with acute purulent synovitis, chronic purulent synovitis and purulent arthritis of the joints of the fingers. Of these, acute purulent synovitis in 7 animals and 23.4% of these common joint pathologies, chronic purulent synovitis in 17 animals (56.6%) and 6 (20%) animals showed the onset and clinical manifestations of purulent arthritis. Characterized by synovitis of the joint, general weakness, loss of appetite, severe pain on palpation, an increase in general body temperature and local temperature.